2011
DOI: 10.3144/expresspolymlett.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Efficient one-step melt-compounding of copolyetheramide/pristine clay nanocomposites using water-injection as intercalating/exfoliating aid

Abstract: Abstract. Polyether-block-amide (PEBA) /clay nanocomposites were prepared water-assisted by twin-screw extrusion. Both organomodified and pristine (i.e. purified but non-modified) montmorillonite clays were used. A high-pressure differential scanning calorimetry analysis carried out in the processing conditions demonstrated that PEBA/water blend exhibits some miscibility and that amide blocks and water behave as a single phase. In addition to a significant decrease of the melting temperature, water injected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
(109 reference statements)
1
20
0
Order By: Relevance
“…This might either indicate that hydrolysis is not significant, or that it is compensated by a reduction of thermal degradation, as the hot points are eliminated by the injection of cold water. Overall, those results are consistent with previous studies involving PA6 5,7 or copolyetheramide, 14 which concluded that hydrolysis during water-assisted extrusion processes remained limited, essentially due to short contact times between polymer and water.…”
Section: Oscillatory Rheometrysupporting
confidence: 82%
See 1 more Smart Citation
“…This might either indicate that hydrolysis is not significant, or that it is compensated by a reduction of thermal degradation, as the hot points are eliminated by the injection of cold water. Overall, those results are consistent with previous studies involving PA6 5,7 or copolyetheramide, 14 which concluded that hydrolysis during water-assisted extrusion processes remained limited, essentially due to short contact times between polymer and water.…”
Section: Oscillatory Rheometrysupporting
confidence: 82%
“…Their process was further applied by numerous authors to produce PA6, [5][6][7][8] polypropylene (PP) and [Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.] maleated polypropylene (PP-g-MA), [9][10][11][12] styrene-acrylonitrile (SAN), 13 and copolyetheramide 14 composites based on untreated montmorillonite or other inorganic nanoparticles (e.g., halloysite nanotubes). Delamination of untreated montmorillonite at the nanoscale was readily achieved in PA6.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy is widely used but provides local and qualitative assessment only. Alternatively, dynamic (oscillatory) rheology may provide a semi-quantitative evaluation of the dispersion degree of nanofillers such as carbon nanotubes or layered silicates (montmorillonite among others) in the bulk [8,18,[32][33][34][35]. Also, X-ray diffraction (XRD) analysis allows quantifying the intercalation in the bulk by measuring the clay platelets interlayer distance [35].…”
Section: Assessment Of Clay Dispersion Intercalation and Exfoliationmentioning
confidence: 99%
“…But, it brings forth lower chance for nanoclay modification. As a result, this method is best used only for high surface energy polymers [15,16]. It should also be noted that the use of water in producing polymeric nanocomposites is not only limited to polymer/nanoclay composites; this method can be employed to produce polymeric composites from other particles as well [17].…”
mentioning
confidence: 99%